Immunocompetent truncated E2 glycoprotein of bovine viral diarrhea virus (BVDV) expressed in Nicotiana tabacum plants: A candidate antigen for new generation of veterinary vaccines - Nelson, Guillermo (2012)
The Bovine Viral Diarrhea Virus (BVDV) is the etiological agent responsible for a wide spectrum of clinical diseases in cattle. The glycoprotein E2 is the major envelope protein of this virus and the strongest inductor of the immune response. There are several available commercial vaccines against Bovine Viral Diarrhea (BVD), which show irregular performances. Here, we report the use of tobacco plants as an alternative productive platform for the expression of the truncated version of E2 glycoprotein (tE2) from the BVDV. The tE2 sequence, lacking the transmembrane domain, was cloned into the pK7WG2 Agrobacterium binary vector. The construct also carried the 2S2 Arabidopsis thaliana signal for directing the protein into the plant secretory pathway, the Kozak sequence, an hexa-histidine tag to facilitate protein purification and the KDEL endoplasmic reticulum retention signal. The resulting plasmid (pK-2S2-tE2-His-KDEL) was introduced into A. tumefaciens strain EHA101 by electroporation. The transformed A. tumefaciens was then used to express tE2 in leaves of Nicotiana tabacum plants. Western Blot and ELISA using specific monoclonal antibodies confirmed the presence of the recombinant tE2 protein in plant extracts. An estimated amount of 20 μg of tE2 per gram of fresh leaves was regularly obtained with this plant system. Injection of guinea pigs with plant extracts containing 20 μg of rtE2 induced the production of BVDV specific antibodies at equal or higher levels than those induced by whole virus vaccines. This is the first report of the production of an immunocompetent tE2 in Nicotiana tabacum plants, having the advantage to be free of any eventual animal contaminant.